THE APPLICATION OF EMULSION LIQUID MEMBRANE (ELM) ON THE CHROMIUM EXTRACTION - I. Hartati; M. E. Yulianto (JURNAL ILMIAH MOMENTUM, 2007)
One of heavy metal compounds that widely used in industry is Chromium. Chemical or biological treatments are not yet able to deal with  the problems caused by heavy metal pollution. Taking the expensive heavy metal such as chromium, nickel, and mercury from the waste water and then re-used the recovered heavy metal is the effective method in treating waste water with expensive heavy metal on it. One of the methods that can be applied is by using Emulsion liquid Membrane (ELM).The objectives of this research were to determine the most influencing variable and to determine the  optimum condition of the extraction process. The process variables tested in this research conducted were carrier concentration, external phase acidity and stripper concentration on the internal phase. While the fixed variables were ratio of emulsion and  external phase volume and agitation time of the permeation step. The research was conducted in a stirred tank and divided into three  major step which were the membrane stability test, the determination of the variable that gave the most dominant influence to the chromium recovery on the membrane condition which was achieved from the first step, and the third step was optimization  of the most influencing variable on the chromium extraction process, while the optimum condition for the chromium extraction from liquid waste water were the concentration of chromic acid in the  external phase was 600 mg/L, the stripper concentration in the in  internal phase was 3 M, agitation time was 15 minutes, the volume ratio of the emulsion and the external phase was 1:3 and the carrier concentration was 0.049%. Key words : chromium, emulsion liquid membrane, extraction